The development of an algorithm and a model through image processing and remote sensing techniques for assessing environmental impacts of routine carbon footprint in Peninsular Malaysia. - Mat Jafri, Mohd. Zubir (Universiti Sains Malaysia, 2015)
This research develope the prediction models which analyze and compute the CO2 emission in Malaysia. Each prediction model for C02 emission is analyzed based on three main groups which is transportation, electricity production and consumption as well as residential and industry. The prediction models was generated using data obtained from World Bank Open Data. Partial least square and best subset method were used to remove irrelevant data and followed by multi linear regression to produce the prediction models.